The Effects of Mergers and Acquisitions on the Performances of Acquiring Firms: Evidence from the UK Telecommunication Industry - SHI, Suocheng (2015)
Telecommunication industry is an innovative industry and becomes more and more important in our daily life. It is said that the furthest distance between people is without internet. In response to the globalization and industrial deregulation, telecommunication industry becomes the active player in merger and acquisition To investigate whether merger will bring the abnormal returns to bidders, the event study methodology is adopted. Market-adjusted model and mean-adjusted model are used to calculate abnormal returns over event windows [-1, +1], [-2, +2] and [-5, +5]. From the event study, it shows that bidders from telecommunication enjoy positive abnormal returns around the announcement date. From the univariate analysis, it shows that related mergers, cross-border mergers, mergers that pay with cash, mergers that have larger relative size of target, value acquirers, and mergers that acquire private target have positive returns. From the multivariate analysis, most of the findings are consistent with the univariate analysis. The most contradict finding is that mergers that have a larger relative size of target generate lower returns.